Does delayed exercise-based priming improve subsequent athletic performance? A systematic review and multilevel meta-analysis - Zitao Wang; Haitao Li; Wanyuan Xia; Ziqi Jin; Shiping Fu; Zhenxin Nie (PLoS ONE, 2026)
This systematic review and multilevel meta-analysis examined whether delayed exercise-based priming improves subsequent athletic performance. Following PRISMA 2020 principles, 3,095 records were identified; after removing 1,107 duplicates, 1,988 unique records were screened, 212 full-text reports were assessed, 186 reports were excluded at eligibility, and 26 studies were included. Eighteen studies contributed 46 effect sizes to the quantitative synthesis. Risk of bias was assessed with RoB 2 principles calibrated for crossover exercise trials, and certainty was evaluated using GRADE. A three-level random-effects model showed a small positive average effect of delayed priming on subsequent performance (g = 0.232, 95% CI [0.092, 0.372], p = .002), with cluster-robust inference supporting the same conclusion (p = .004). The prediction interval crossed zero (−0.265 to 0.730), and the overall certainty of evidence was low. Delayed exercise-based priming can be used as a practical competition-day strategy when embedded in planned preparation windows, although protocol selection and athlete response should be checked in training before competition use.